Digital rhetoric in Indonesian political campaigns: a multimodal discourse analysis of social media narratives - Eka Fitri Hastuti (Indonesian Journal of Language and Communication Studies, 2026)
Background: Today’s political campaigns increasingly rely on multimodal rhetoric to shape public perception and voter behavior through social media platforms. Objective: This study aims to analyze the digital rhetoric strategies of Indonesian presidential candidates Ganjar Pranowo and Anies Baswedan during the 2024 election campaign on Instagram and Twitter. Method: Using a qualitative approach with Critical Multimodal Discourse Analysis (CMDA), the research examined 30–50 official posts per candidate, focusing on visual, textual, and symbolic elements. Results: The results show that Ganjar constructs a populist-technocratic identity through inclusive imagery and civic-nationalist framing, while Anies uses religious and moral narratives to mobilize faith-based voters. Ganjar’s participatory content appeals to affective publics via humor and nostalgia, whereas Anies elicits higher engagement through sermon-like storytelling and visionary rhetoric. These narrative patterns reflect distinct ideological alignments and are shaped by the structural foundations of each candidate’s political-religious coalition. Implication: The findings suggest that digital rhetoric functions not only to inform but also to emotionally mobilize and ideologically position voters within polarized digital communities. Novelty: The novelty of this study is the exploration for ethical and strategic awareness in designing political messages in digitally networked democracies.